Modeled ocean circulation in Nares Strait and its dependence on landfast‐ice cover. Issue 12 (17th December 2015) - Shroyer, Emily L.; Samelson, Roger M.; Padman, Laurie; Münchow, Andreas
Abstract: Two simplified ocean simulations are used to study circulation and transport within Nares Strait. The simulations are similar, except that one included a coupled sea ice model that effectively established a landfast ice cover throughout the simulation year. Comparison between the ocean‐only and ocean‐ice simulations reveals a systematic change in the current structure, reminiscent of the seasonal shift under mobile and landfast ice previously observed in Nares Strait. A surface‐intensified jet, which carries low‐salinity water along the strait's centerline, develops within the ocean‐only simulation. The current structure under landfast ice is characterized by a subsurface jet located along the western side with low‐salinity surface water distributed along the eastern side of the strait. Intermediate salinity water is offset to the west in the ice‐ocean simulation relative to the ocean‐only simulation, while high‐salinity water (>34.8) is constrained to recirculations that are located north and south of a sill in Kane Basin. The simulations, combined with an idealized, semianalytical model, suggest that the structural shift is caused by the surface Ekman layer beneath the landfast ice and the associated eastward advection of near‐surface low‐salinity water and westward movement of the jet. Temporal variability in the ocean‐ice simulation is dominated by the remote response to the time‐dependent northern boundary conditions. In contrast, the ocean‐only simulation favors an instability and additionally responds to local surface wind forcing, which enhances the variability within the strait above that imposed at the boundaries. Key Points: Simulations reproduce observed seasonal shift in ocean structure in Nares Strait Shift tied to differing surface friction associated with mobile and landfast ice Distribution of heat and salt is systematically altered by the presence of ice